Breakthrough in Heart Failure therapy: LCZ696 combining ACE-Neprilysin inhibition - Lahiry, Sandeep; Sinha, Rajasree; Choudhury, Shouvik; Mukherjee, Ayan (Asian Journal of Medical Sciences, 2017)
Background: Current Heart failure (HF) pharmacotherapy has been unsatisfactory in halting disease progression completely. Aims and Objective: To evaluate the role of LCZ696, a recent FDA-approved ACE -Neprilysin inhibitor (ARNi) in the management of HF from available trial data. Materials and Methods: Trial data on ‘LCZ696’ was assessed using PubMed search. Methodological filters were applied to limit retrieval to ‘Randomized Controlled Trial’ (RCT). Bibliographic databases with ‘Human’ data were selected. Trial data comparing ‘LCZ696’ to other drugs or placebo were accessed in full-text. CONSORT guidelines were used for quality assessment. Incomplete methodology, results in abstract form, duplicate publications were excluded. Data extraction forms were piloted and used to obtain uniform quality of data. Results: Multi-centric trial data (n=2) revealed noticeable benefits with ‘LCZ696’ in patients with HF with reduced ejection fraction (HFrEF), reducing cardiovascular death or hospitalization for HF by 20%; cardiovascular deaths by 20%; hospitalization for HF by 21% ; all cause mortality reduction by 20% as compared to ACE inhibitors (ACEi) (PARADIGM-HF; n=8442). Angioedema was notably absent. Decrease in high sensitivity Troponin-T, improvement in N-terminal-pro-BNP and left atrial dimensions suggested reduction of myocardial injury in HF with preserved ejection fraction (HFpEF) (PARAMOUNT trial; n=301). Conclusion: There is convincing evidence of the role of novel ARNi (Angiotensin receptor – Neprilysin Inhibitors) in HF pharmacotherapy. Its role in other cardiovascular conditions merits assessment. Asian Journal of Medical Sciences Vol.8(1) 2017 1-4